MODERNIZATION OF TRACKED VEHICLE RUNNING GEARS - V. A. Korobkin; A. Ya. Kotlobai; V. P. Boikov; A. A. Kotlobai; V. F. Tamelo (Наука и техника)
The paper contains some proposals pertaining  to modernization of tracked vehicle running gears, bogie hydro-pneumatic suspension, methodology  for bench-tests and description of test-bench equipment which is applied for testing bogie hydro-pneumatic suspension. Test results of a hydro-pneumatic spring with parameter stabilization system are given in the paper.The paper presents  description of tracked vehicle running gears with bogie hydro-pneumatic suspension which is equipped with a system for stabilizing a road clearance. Testing results of the gears being part of a test mule are cited in the paper.